High charge acceptance through interface reaction on carbon coated negative electrode for advanced lead-carbon battery system. (1st February 2019) - Sadhasivam, T.; Park, Mi-Jung; Shim, Jin-Yong; Jin, Jae-Eun; Kim, Sang-Chai; Kurkuri, Mahaveer D.; Roh, Sung-Hee; Jung, Ho-Young
Abstract: In this research, the interfacial effect between the carbon layer and the negative electrode surface is evaluated as a hybrid electrode with higher charge acceptance for the advanced lead-carbon battery (ALC-battery) system. The P-60 (activated carbon) material, with high specific surface area (1787 m 2  g −1 ) and higher electrical conductivity (98.85 S cm −1 ), is considered an efficient activated carbon in the present investigations and deposited on the negative electrode. Compared to the conventional lead-acid battery system, the carbon coated negative electrode of ALC-battery system exhibited higher capacity at the applied higher charge/discharge current. The efficient performance of the ALC-battery is mainly influenced by the thin layer of carbon on the active electrode surface, which induces higher charge acceptance. Furthermore, the ALC-battery showed an outstanding lifespan performance compared to the conventional lead-acid battery system in long-term operations. The resulting cycle life stability of lead-acid battery and ALC-battery is 2230 and 6780 cycles, respectively. The significant performance of the ALC-battery is mainly attributed by synergistic mechanism in hybrid electrode, which is resulted from interfacial effect. The likely synergetic reactions arises by carbon layer is (i) higher charge acceptance, (ii) controlled the formation of PbSO4 crystallite in the electrode surfaces, (iii) improved electrochemical performances and Pb redox reaction due to higher electrical conductivity properties. Thus, it can be concluded that the carbon layer deposited on the negative electrode in the ALC-battery is an efficient approach for energy storage, with increased power, capacity, and enhanced cycle life stability. Graphical abstract: Image 1 Highlights: ALC-battery can be effectively considered for Idle Stop and Go vehicles. Synergistic effect in negative electrode enhances the ALC-battery performances. Charge acceptance of the battery is increased by carbon layer on negative electrode. Carbon layer can control the formation of larger PbSO4 on surface of the electrode. Lifespan of ALC-battery is 3 times higher than conventional lead-acid battery.